(untitled) (Research, Society and Development, 2021)
Environmental stresses can influence the germination and initial growth of plant species. The understanding of these responses can contribute to the understanding of the establishment of species in the environment or even, subsidize the production of seedlings. This study investigated the influence of salinity on twinning and biometrics in the early stages of Cenostigma pyramidale. The study was carried out at the Academic Unit of Serra, Serra Talhada - Pernambuco. The seeds of Cenostigma pyramidale (Tul.) Gagnon & G.P. Lewis were submitted to pre-germinative treatments by means of mechanical scarification with wooden sandpaper No. 150. Then the treated seeds were sown in cell trays made of polypropylene containing soil and a thin superficial layer of vermiculite for the emergence of seedlings. Upon sowing, the species was submitted to three levels of salinity: N1 - 0.18 (CONTROL); N2 - 1.52 and N3 - 2.22 dS.m-1. The adopted design was completely randomized with four replications. Water replenishment was performed daily, as well as counting the number of seedlings that emerged. With these data it was obtained: percentage of seedling emergence (PE) and the emergence speed index (IVE). Additionally, height (ALT), collar diameter (DIAM), number of fully expanded leaves (NFCE) and dry plant biomass (BST) were obtained. Our results showed that the increase in salinity levels promoted reductions in IVE and PE of Cenostigma pyramidale seeds. However, no changes were observed in the biometric aspects and the initial biomass accumulation of the species.